If Nudges Treat their Targets as Rational Agents, Nonconsensual Neurointerventions Can Too - Douglas, Thomas (Ethical theory and moral practice, 2022)
Andreas Schmidt and Neil Levy have recently defended nudging against the objection that nudges fail to treat nudgees as rational agents. Schmidt rejects two theses that have been taken to support the objection: that nudges harness irrational processes in the nudgee, and that they subvert the nudgee’s rationality. Levy rejects a third thesis that may support the objection: that nudges fail to give reasons. I argue that these defences can be extrapolated from nudges to some nonconsensual neurointerventions; if Schmidt’s and Levy’s defences succeed, then some nonconsensual neurointerventions neither harness irrationality, nor subvert rationality, nor fail to give reasons. This, I claim, poses a challenge both to opponents of nonconsensual neurointerventions, and to defenders of nudging.